Peningkatan Motivasi Belajar IPS Melalui Penerapan Strategi Make a Match dengan Media Gambar pada Siswa Kelas IV SD Muhammadiyah Baturan Tahun Ajaran 2015/2016 - Rifa'i, Syaifuddin; , Dra. Risminawati, M.Pd (2016)
This type of research is classroom action research. The purpose of this classroom action research is to increase motivation and learning social science subject through the use of strategies Make a Match strategy with image medias on fourth grade students of SD Muhammadiyah Baturan. The research subject is the class teacher and the fourth grade students at 25 students. Data collection techniques used are observation, interviews, documentation. Data analysis technique used is the technique of interactive analysis of selected data reduction, data presentation and conclusion. Based on the research result: students 'motivation in the initial conditions before the action was 53.40% in the first cycle of meeting 1 61.00% 2 meeting increased to 71.00%, the second cycle of meeting 1 at 76.20%, next on the meeting 2, the students' motivation increased to 79.00 %. Based on the result of the study it can be concluded that the application of learning strategy using Make a Match with image medias can increase motivation to learn in social studies of thr fourth grade students of SD Muhammadiyah Baturan the school year 2015/2016. Keywords: Motivation, Make a Match, Media Image